RANCANG BANGUN MESIN PENGGILING UDANG KERING - Ryan Eberson Garingging; Tambos A. Sianturi; Jhon Supriadi Purba (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Terasi or Belacan is a cooking spice made from fermented rebon fish or shrimp, shaped like dough or paste and black-brown in color, sometimes adding coloring ingredients to make it reddish. Belacan is an important cooking spice in Southeast Asia and Southern China. In essence, Belacan is the result of the preservation process of fish or shrimp which is prepared with a mixture of other ingredients so that it can be used as an additional ingredient in several typical dishes.The grinding process using the traditional method in Teluk Pulai Village, Pasir Limau Kapas District, Rokan Hilir Regency, did not get satisfactory results because apart from the results being less than optimal, it also took a long time and still used human power to grind. With the increasing development of science and technology, it has an impact and influence by continuing to increase the need for various tools to make work easier and smoother in various fields, both as complements and as main products. So this becomes a reference for the author to design a dry shrimp grinding machine which will later be able to produce shrimp seasoning which will be the raw material for Belacan. It is hoped that this shrimp grinding machine can help Belacan producers in the Belacan planning process, so that producers can save time and increase their Belacan production results.